Histological study of the central or primary lymphoid tisues of broiler chickens - Md. Abdul Masum; Md. Zahirul Islam Khan; Morsheda Nasrin; M.N.H. Siddiqi (J. Expt. Biosci. 4(1):69-72, January 2013, 2013)
[Histology was performed in the central or primary lymphoid tisues (thymus and bursa of